The Influence of Leadership Style, Compensation, and Organizational Culture on Employee Performance with Work Motivation as an Intervening Variable (Empirical in Semarang Islamic Financial Institutions) - Amin Sadiqin (LAFADZ JAYA Publisher, 2023)
This study aims to determine the effect of leadership style, compensation and organizational culture on employee performance at Islamic Financial Institutions in Semarang City with work motivation as an intervening variable. This sample uses Islamic financial institutions, namely BMT Beringharjo, BMT BIF and Bank Muamalat with a total of 40 respondents. From BMT Beringharjo 3 employees, BMT BIF 25 employees and Bank Muamalat 12 employees.Based on the analysis that has been done, the results show that leadership style has a positive effect on employee performance, compensation has a negative effect on employee performance, organizational culture has a negative effect on employee performance, leadership style has a positive effect on work motivation, compensation has a positive effect on work motivation, organizational culture has an effect positive effect on work motivation, work motivation has a positive effect on employee performance, leadership style has a positive effect on employee performance through work motivation, compensation has a positive effect on employee performance through work motivation, and organizational culture has a positive effect on employee performance through work motivation in Islamic financial institutions in Semarang city.